2021
DOI: 10.3390/biom11111663
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Metabolic Determinants of Atrial Fibrillation in a General Population Sample: The CHRIS Study

Abstract: Atrial fibrillation (AF) is a supraventricular arrhythmia deriving from uncoordinated electrical activation with considerable associated morbidity and mortality. To expand the limited understanding of AF biological mechanisms, we performed two screenings, investigating the genetic and metabolic determinants of AF in the Cooperative Health Research in South Tyrol study. We found 110 AF cases out of 10,509 general population individuals. A genome-wide association scan (GWAS) identified two novel loci (p-value &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…To date, a limited number of studies have evaluated the relationship between circulating metabolites and AF. 38 , 39 , 40 , 41 , 42 , 43 , 44 In the community‐based ARIC (Atherosclerosis Risk in Community) Study, glycolithocholate sulfate and glycocholenate sulfate (bile acid metabolites) in Black individuals 38 and pseudouridine and uridine (pyrimidine metabolism), and acisoga (polyamine metabolism) were associated with incident AF. 39 However, a prior FHS study found no association of AF risk with the 217 metabolites in the sample studied with 156 AF events with 10 years of follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a limited number of studies have evaluated the relationship between circulating metabolites and AF. 38 , 39 , 40 , 41 , 42 , 43 , 44 In the community‐based ARIC (Atherosclerosis Risk in Community) Study, glycolithocholate sulfate and glycocholenate sulfate (bile acid metabolites) in Black individuals 38 and pseudouridine and uridine (pyrimidine metabolism), and acisoga (polyamine metabolism) were associated with incident AF. 39 However, a prior FHS study found no association of AF risk with the 217 metabolites in the sample studied with 156 AF events with 10 years of follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Data processing, read alignment and QC were conducted as detailed previously. 23,24 We retained 3422 samples with a post-QC mean target coverage of 68.4X.…”
Section: Methodsmentioning
confidence: 99%
“…Data processing, read alignment and QC were conducted as detailed previously. 23,24 We retained 3422 samples with a post-QC mean target coverage of 68.4X. WES data were used as a population-specific reference panel for genotype imputation onto the whole CHRIS sample as reported previously.…”
Section: Genomicsmentioning
confidence: 99%
“…Some recent work has been published evaluating the impact of age, sex and diet, amongst others, on the human metabolome (Verri Hernandes et al, 2022). Moreover, gene-metabolite associations (König et al, 2022), as well as genetic and metabolomic determinants of disease (Emmert et al, 2021), have been investigated. We performed a general exploratory analysis of the data set to identify relevant factors affecting the plasma proteome and found hormonal contraceptives to be the main factor explaining the variation in a human plasma proteome from European individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work, we have been evaluating the impact of age, sex and diet, amongst others, on the human metabolome (Verri Hernandes et al, 2022). Moreover, gene-metabolite associations (König et al, 2022), as well as genetic and metabolomic determinants of disease (Emmert et al, 2021), have been investigated. Using Scanning SWATH (Messner et al, 2021) acquisition on Triple TOF 6600 Instruments (Sciex) we created a MS-based plasma proteomics data set with low technical variability for n = 3,632 CHRIS participants.…”
Section: Introductionmentioning
confidence: 99%